Exploring density‐ and frequency‐dependent interactions experimentally: An r program for generating hexagonal fan designs. Issue 5 (2nd April 2020) - Rozins, Carly; Hood, Michael E.; Cho, Jae Hoon; Antonovics, Janis
Abstract: Species interactions and diversity are strongly impacted by local processes, with both the density of a focal species and its frequency in the community having an impact on its growth, survival and fecundity. Yet, studies that attempt to control for variation in both frequency and density have traditionally required a large number of replicates. Hexagonal fan designs can include a range of both densities and frequencies in a single plot, providing large economies in space and material for studying local interactions such as competition and disease transmission. However, in practice such experiments can be difficult to plan and implement. This study presents an R program whereby the user can rapidly view a variety of designs and determine the configurations that work best with their space and material constraints. Simple instructions for implementing the fan in any design setting are also provided. We illustrate the implementation of a simple form of the hexagonal fan design in a field experiment to assess the impact of host density on pollinator movement and disease transmission.